ANALISIS NILAI TAMBAH DAN KEUNTUNGAN PENGOLAHAN BIJI KOPI DI PT FORTUNA INTI ALAM KOTA MANADO (Analysis of the Added Value and Profit of Coffee Bean Processing at PT Fortuna Inti Alam, Manado City) - Maria Meylan Lauw; Agnes E. Loho; Leonardus R. Rengkung (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This study aims to analyze the added value and benefits of processing coffee beans into ground coffee at PT. Fortuna Inti Alam. The research location was conducted at PT. Fortuna Inti Alam Highway Manado – Bitung, Maumbi Village Dusun III, North Minahasa Regency. The data used in this study comes from primary data and secondary data. Primary data is data obtained di-rectly from respondents (coffee business owners) while secondary data is obtained from related agencies, literature or literature, articles from journals related to this research. The analysis used is added value analysis and profit analysis. The results showed that the processing of coffee beans into ground coffee provided a gross added value of Rp. 1,803,171., net added value of Rp. Rp. 1,580,742 and obtained an added value per raw material of Rp. 34,724/Kg. The profit received is Rp. 830,081,092 which was obtained from a total receipt of Rp. 3,337,422,000 and a total cost of Rp 2,507,340,908.